How to Design Auditor Liability When Judges Suffer from Hindsight Bias - Jochen Bigus; Nadine Georgiou (Abacus, 2025)
There is evidence that judges evaluate auditor effort with hindsight bias, overestimating the likelihood that the auditor has not met the standard of due care. In an analytical analysis, this paper shows that auditors will rationally anticipate judges' hindsight bias and will thus likely exert excessive effort in the first place. Furthermore, the paper shows that, counterintuitively, (a) capping liability and (b) lowering the standard of due care to gross negligence are generally not helpful remedies to efficiently counteract hindsight bias. Indeed, a debiasing strategy intended to mitigate judges' hindsight bias, such as by providing appropriate training, may actually cause excessive auditor effort. However, if the legislator tightens the standard of due care sufficiently, this will provide efficient incentives. At the same time, tightening the standard of due care is not a suitable remedy for a different form of hindsight bias, which induces a judge to find the auditor's behaviour reckless and to award punitive damages. Consequently, the proper design of remedies to mitigate the effects of judges' hindsight bias depends on whether or not punitive damages are allowed.
Keywords: 330; Auditor liability; Audit quality; Judges' hindsight bias; Negligence rule; Psychological bias; Punitive damage